DETERMINANTS AND CLASSIFICATIONS OF ONLINE SHOPPING CONSUMERS"™ PURCHASE INTENTION IN INDONESIA - Nugraheni, Reninta Dewi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
Online shopping is still growing significantly, which is an upward trend for e-commerce platforms. It has grown in popularity among consumers for a number of reasons, driving Indonesian consumer behavior. This study aims to identify determinants and classifications of Indonesian online shopping consumers"™ purchase intention using the decision tree methodology. The notion underpinning this study is the phenomena of online shopping as a consumer behavior transition in Indonesia which has increased gradually over the last decades. The data was collected using a structured questionnaire and 820 respondents participated in this study. Then, the data was analyzed using C5.0 and CART 5.0 algorithms. The results show that the most influential determinants of the frequency of online shopping include the consumers"™ occupation, choice of e-commerce platforms, product origin, and product quality. The influence of several factors on customers' intentions to engage in shopping online can be determined, including job status, e-commerce platform, product sources, and product quality.JEL: L81, L86, Q5.